Accuracy of Nodal Positivity in Inadequate Lymphadenectomy in Pancreaticoduodenectomy for Pancreatic Ductal Adenocarcinoma: A Population Study Using the US SEER Database - Wang, Weishen; Shen, Ziyun; Shi, Yusheng; Zou, Siyi; Fu, Ningzhen; Jiang, Yu; Xu, Zhiwei; Chen, Hao; Deng, Xiaxing; Shen, Baiyong (Frontiers in Oncology, 2019)
Objectives: The optimal number of the examined lymph nodes (ELNs) in pancreaticoduodenectomy for pancreatic ductal adenocarcinoma has been widely studied. However, the accuracy of nodal positivity for the patients with inadequate lymphadenectomy is still unclear. The purpose of our study was to determine the accuracy of the number of positive nodes reported for patients with 1–3 positive nodes and the probability that 4 or more nodes could be positive along with tumor size and number of nodes examined. Methods: We obtained data on patients who underwent pancreaticoduodenectomy for resectable pancreatic ductal adenocarcinoma diagnosed during 2004–2013 from the US Surveillance, Epidemiology, and End Results registry. An mathematical model based on Hypergeometric Distribution and Bayes' Theorem was used to estimate the accuracy. Results: Among the 9,945 patients, 55.6% underwent inadequate lymphadenectomy. Of them, 1,842, 6,049, and 2,054 had T1, T2, and T3 stage disease, respectively. The accuracy of the number of observed positive nodes increased as the number of ELNs increased and the tumor size decreased. To rule out the possibility of N2 stage (4 and more positive nodes), there should be at least 13 ELNs for the patients with 1 observed positive lymph node and 14 for the patients with 2. Conclusion: Inadequate lymphadenectomy could result in underestimation of the N stage, and this would have adverse impact on recurrence, efficacy of postoperative treatment, and even overall survival. This model combined with the observed positive lymph nodes, the number of ELNs, and tumor size could provide a more accurate determination of nodal positivity of these patients.